2019
DOI: 10.1029/2018ja025969
|View full text |Cite
|
Sign up to set email alerts
|

Substorm Onset Latitude and the Steadiness of Magnetospheric Convection

Abstract: We study the role of substorms and steady magnetospheric convection (SMC) in magnetic flux transport in the magnetosphere, using observations of field-aligned currents by the Active Magnetosphere and Planetary Electrodynamics Response Experiment. We identify two classes of substorm, with onsets above and below 65 • magnetic latitude, which display different nightside field-aligned current morphologies. We show that the low-latitude onsets develop a poleward-expanding auroral bulge, and identify these as substo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 56 publications
(113 reference statements)
4
23
0
Order By: Relevance
“…An increase in Λ with more negative SYM-H is apparent in many of the distributions, as described by Schulz (1997), Milan, Hutchinson et al (2009, and Milan (2009) trend to more negative SYM-H is clear, especially for driven and recovery phases. The distribution for multiple intensifications appears to be a high-Λ extension of the driven phase distribution (in agreement with Milan et al [2019]). The growth and expansion phase distributions cut off above Λ ≈ 25°, whereas the driven and multiple intensifications distributions extend to 28°.…”
Section: On Averagesupporting
confidence: 79%
See 1 more Smart Citation
“…An increase in Λ with more negative SYM-H is apparent in many of the distributions, as described by Schulz (1997), Milan, Hutchinson et al (2009, and Milan (2009) trend to more negative SYM-H is clear, especially for driven and recovery phases. The distribution for multiple intensifications appears to be a high-Λ extension of the driven phase distribution (in agreement with Milan et al [2019]). The growth and expansion phase distributions cut off above Λ ≈ 25°, whereas the driven and multiple intensifications distributions extend to 28°.…”
Section: On Averagesupporting
confidence: 79%
“…Panels (a) and (b) of Figure 1 show keograms of AMPERE FACs along the dawn-dusk meridian of the Northern and Southern Hemispheres. The up/down pairs of R1 and R2 currents can be seen at both dawn and dusk, varying in magnitude with the strength of convection and moving in colatitude as the polar cap expands and contracts (Clausen et al, 2012;Milan, 2013;Milan et al, 2017Milan et al, , 2019. We use the radius of a circle fitted to the boundary between R1 and R2 FACs, determined using the method of Milan et al (2015), as a proxy for F PC .…”
Section: Parametersmentioning
confidence: 99%
“…Figure 3a indicates that substorms are slightly stronger for large IMF 𝐴𝐴 |𝐵𝐵𝑦𝑦| than for small 𝐴𝐴 |𝐵𝐵𝑦𝑦| . This result is consistent with the observation that substorms occur at lower latitudes for large 𝐴𝐴 |𝐵𝐵𝑦𝑦| (Figure 1), as it has been shown that substorms occurring at lower magnetic latitudes are more intense in terms of auroral brightness (Milan et al, 2010) and ionospheric currents (Holappa et al, 2014;Myllys et al, 2015;Milan et al, 2019;Tanskanen et al, 2002).…”
Section: Substorm Strengthsupporting
confidence: 92%
“…We conclude that this result may be related to a phenomenon known as sawtooth events or low-latitude onset substorms (Milan et al, 2019;Walach & Milan, 2015). It is common for large, quasi-periodic substorms to occur with a low-latitude onset when the solar wind driving is high and prolonged, and the Sym-H index is enhanced, which are often also termed sawtooth events (Belian et al, 1995;Cai & Clauer, 2013;Milan et al, 2019;Noah & Burke, 2013;Walach & Milan, 2015).…”
Section: Relationship To Substorms and Sawtooth Eventsmentioning
confidence: 79%